2021
DOI: 10.15405/ejsbs.287
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles Faced by Students in Making Sense of Fractions

Abstract: The learning of fractional concepts is one of primary school students’ first experiences with a mathematics concept beyond the fundamental four basic operators. However, research has shown that students faced great difficulty in learning fractions which, to a large extent, inhibits their intuitive knowledge of it. The learning of fractions is foundational to the understanding of many more advanced areas of mathematics and science. Examining why they face problems making sense of fractions and what can be done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…They argued that this was due to an absence of strategies for deriving a solution. Among the reasons why students are not able to use heuristics is that mathematics instruction currently is too focused on procedural paradigm orientation instead of providing the "problem-solving tools" that would allow the students to be adaptative to changing needs towards the development of mathematical thinking (Singh et al, 2017). Kusdinar et al (2017) found that the teacher does introduce various problems to the students but does not explicitly provide the necessary tools to deal with situations when the solution is not obvious.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…They argued that this was due to an absence of strategies for deriving a solution. Among the reasons why students are not able to use heuristics is that mathematics instruction currently is too focused on procedural paradigm orientation instead of providing the "problem-solving tools" that would allow the students to be adaptative to changing needs towards the development of mathematical thinking (Singh et al, 2017). Kusdinar et al (2017) found that the teacher does introduce various problems to the students but does not explicitly provide the necessary tools to deal with situations when the solution is not obvious.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Salah satu hasil penelitian menyatakan bahwa pecahan adalah salah satu dari aspek-aspek yang paling sulit untuk dipahami dan diajarkan, dan pecahan mendominasi bagian dari Kurikulum Nasional Dasar. Siswa menghadapi kesulitan besar dalam mempelajari pecahan yang, sebagian besar, menghambat pengetahuan intuitif mereka (Agnesti & Amelia, 2021;Singh et al, 2021). Kesulitan siswa tersebut berkaitan dengan tidakmampuan siswa dalam membuat model matematika yang berkaitan dengan lambang pecahan karena siswa kurang memahami konsep pembilang dan penyebut serta kurang memahami unsur yang diketahui MI P-ISSN: 1829-877X E-ISSN: 2685-9033 dan penyampaian konsep pecahan langsung ke contoh abstrak (Musdhalifah et al, 2013;N.…”
Section: Pendahuluanunclassified
“…Distintos estudios muestran que el aprendizaje de las fracciones resulta difícil para muchos niños, y un porcentaje notorio de ellos sólo incorpora las nociones más básicas de este concepto (Hansen et al, 2017;Jordan et al, 2017;National Center for Education Statistics, 2012;National Mathematics Advisory Panel, 2008;Singh et al, 2021). Identificar los factores que caracterizan y distinguen a los estudiantes que experimentan obstáculos en el aprendizaje de las fracciones, respecto de aquellos que alcanzan una comprensión que se adecúa o supera lo esperable conforme a la instrucción recibida, permitiría planificar y diseñar estrategias didácticas que mejoren el proceso de enseñanza-aprendizaje de éstas.…”
Section: Introductionunclassified